2009
DOI: 10.1111/j.1574-6976.2008.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Global phenotypic characterization of bacteria

Abstract: The measure of the quality of a systems biology model is how well it can reproduce and predict the behaviors of a biological system such as a microbial cell. In recent years, these models have been built up in layers, and each layer has been growing in sophistication and accuracy in parallel with a global data set to challenge and validate the models in predicting the content or activities of genes (genomics), proteins (proteomics), metabolites (metabolomics), and ultimately cell phenotypes (phenomics). This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
330
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(335 citation statements)
references
References 86 publications
4
330
0
1
Order By: Relevance
“…Preliminary results from Biolog-AN plates (data not shown) indicated that not only uptake and oxidation of amino acids, but also the ability to transport and oxidize many other compounds was reduced early during irradiation. The ability to reduce substrates in the assay was lost simultaneously for all C-sources, again indicating that the final step of the respiratory chain is inactivated at this time rather than single transport systems within the membrane (Bochner, 2009). …”
Section: Discussion Changes In Cellular Energy Metabolism During Uva mentioning
confidence: 99%
“…Preliminary results from Biolog-AN plates (data not shown) indicated that not only uptake and oxidation of amino acids, but also the ability to transport and oxidize many other compounds was reduced early during irradiation. The ability to reduce substrates in the assay was lost simultaneously for all C-sources, again indicating that the final step of the respiratory chain is inactivated at this time rather than single transport systems within the membrane (Bochner, 2009). …”
Section: Discussion Changes In Cellular Energy Metabolism During Uva mentioning
confidence: 99%
“…In total, these 10 PM plates contained 237 toxins (including antibacterial agents), with each toxin present at four concentrations (24). Growth in each toxin-containing well could be monitored by purple color development because of the presence of a tetrazolium indicator dye (25). A negative control (E. coli harboring the empty ASKA vector, pCA24N-NoIns) was used to inoculate a second set of PM plates in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria grown on solid medium are suspended in a minimal, defined medium (Bochner, Gadzinski and Panomitros, 2001;Bochner, 2009). The phenotypic microarray is carried out in 96-well plates, with each of the wells containing a different nutrient.…”
Section: Phenotypic Microarray Technologymentioning
confidence: 99%